Clinical Improvement in Autism Spectrum Disorder Symptoms Following Hyperbaric Oxygen as Adjuvant Therapy in a 12-Year-Old Boy - Ni Komang Sri Dewi Untari; Pramita Anindya Nugraheni; Renny Agustin; Reza Mardiana Ayu Oktavia; Rheina Hasna Rantika; Rifqi Athaya Vinanta Hadi; Rina Mega Utami; Ronald Pratama Adiwinoto (AKSONA, 2026)
Highlight: The potential role of hyperbaric oxygen therapy (HBO) as an adjunctive treatment for autism spectrum disorder (ASD), demonstrating significant improvements in clinical symptoms. By exploring the plausible mechanisms of HBO, the manuscript underscores the importance of further research and clinical trials to validate its efficacy and safety in the ASD population. This study adds to the literature advocating for innovative therapeutic strategies that address the complex interplay of oxidative stress, neuroinflammation, and mitochondrial dysfunction, inviting a personalized treatment approach.   ABSTRACT Introduction:  Autism spectrum disorder (ASD) is a multifaceted neurodevelopmental condition influenced by both genetic predispositions and environmental factors. Its underlying pathophysiology commonly involves oxidative stress, impaired cerebral perfusion, neuroinflammation, immune dysregulation, and mitochondrial dysfunction. Although conventional interventions, such as applied behavior analysis (ABA), are commonly employed, they may yield limited progress for some individuals. Consequently, emerging interventions, such as hyperbaric oxygen therapy (HBO), show promise for enhancing neurological outcomes and warrant further exploration. HBO, a well-established treatment for decompression sickness, is currently being investigated for its potential benefits in various neurological disorders, including ASD. Case: We present a case of ASD in a 12-year-old boy characterized by minimal eye contact, limited expressive language, and restricted, repetitive behaviors. On neurological examination, the patient was alert and capable of spontaneous eye opening, vocalizing incomprehensible words, and, at times, responding to simple commands. Despite undergoing ABA therapy, the patient exhibited limited developmental progress. The patient was subsequently undergoing hyperbaric oxygen therapy (HBO) at 1.3 ATA for 60 minutes for 10 days. Following the completion of HBO therapy, there was a decline in the CARS score from 41.5 (severe) to 29 (mild), the ATEC score from 115 to 68, the platelet count (51,000 / μL), and interleukin-1β levels (181.4 pg/mL). Conclusion: This case highlights the potential of HBO therapy as an adjunctive treatment modality for ASD, offering significant symptomatic improvements in a patient for whom traditional therapies were insufficient. The presumed mechanisms underlying these effects include anti-inflammatory effects and enhanced cerebral oxygen delivery, which may facilitate neuronal recovery and function. Given these findings, further research and clinical trials are warranted to confirm the therapeutic efficacy, long-term benefits, and safety profile of HBO therapy.